Mudanças na bovinocultura leiteira entre os anos 2010 e 2020: um estudo de caso da microrregião de Pitanga - PR - Bini, Luiz Felipe (2023)
The aim of this dissertation is to identify the characteristics and motivations for dairy farmers leaving the business between 2010 and 2020. Dairy farming is a predominant activity carried out by small establishments throughout the country, and this is no different in the Pitanga micro-region, which is mainly characterized by the presence of family labour. This activity contributes directly to increasing the income of municipalities and families. Given the social and economic changes observed on the world stage and in Brazil, and the changes in the behavior of dairy farmers, it became necessary to find out the real motivations behind the changes that are noticeable in this sector of agriculture. The methodology is an explanatory and descriptive study, using primary data (questionnaires) and secondary data via a database to obtain information. The questionnaires were applied in a non-probabilistic way to establishments that stopped producing milk between 2010 and 2020. This is an explanatory study aimed at identifying the factors that determined or corroborated the abandonment of rural dairy farming. The vast majority of producers' perception of the dairy production scenario was similar, with the vast majority pointing to the same factors for the closure of the activity, such as: the price paid for a liter of milk, production costs/inputs and labor. In addition, the lack of family succession is a way of guaranteeing the continuity of the activity, but the departure of young people from the countryside in search of urban centers, coupled with the advanced age of those responsible for the establishments, has left the properties under the control of older individuals, corroborating the decision to leave the activity. In addition to the reduction in the number of establishments dedicated to milk production, there has been an intensification of production on properties that decided to remain, absorbing production in quantity, so it was still possible to increase the total volume of production in the period studied. The strong growth in agriculture was responsible for occupying areas that were used to produce animal feed or pasture, increasing agricultural production rates in soybeans, corn and wheat.